Common Articulatory Errors of English-Speaking Filipinos - Berger, Kenneth W. (Silliman Journal, 2024)
In this study of the English speech habits of four Filipinos, it was found that no consistent omissions or additions of sounds were found, and the few sound omissions followed no. identifiable pattern.